Tangled worlds:the Swedish, the Sámi, and the reindeer - Salmi, A.-K. (Anna-Kaisa); Heino, M. T. (Matti T.) (Springer Nature, 2019)
Abstract Reindeer pastoralism developed among the indigenous Sámi of northern Fennoscandia, but the established colonial relationship with Sweden brought on an expanded use of reindeer. Tradesmen, priests, and officials of Swedish origin benefited from domesticated reindeer in many ways — trading reindeer products and using reindeer as transport during winter trips to marketplaces. Reindeer were, therefore, in many ways focal in the encounters between the Sámi and the Swedish. In this paper, we use zooarchaeology, stable isotope analysis, and ancient DNA analysis to interpret reindeer remains from towns, marketplaces, and agrarian settlements in medieval and early modern northern Fennoscandia. We argue that reindeer played important roles in contacts and encounters. The Sámi, the Swedish, and the reindeer formed a multispecies community. The exploration of the relationships in this multispecies community captures the complexity of human and human-animal relationships in colonial encounters. Moreover, it emphasizes the importance and agency of animals in colonial histories.